LINGO-1 and Neurodegeneration: Pathophysiologic Clues for Essential Tremor. (20th February 2012) - Zhou, Zhi-dong; Sathiyamoorthy, Sushmitha; Tan, Eng-King
Essential tremor (ET), one of the most common adult-onset movement disorders, has been associated with cerebellar Purkinje cell degeneration and formation of brainstem Lewy bodies. Recent findings suggest that genetic variants of the leucine-rich repeat and Ig domain containing 1 (LINGO-1) gene could be risk factors for ET. The LINGO-1 protein contains both leucine-rich repeat (LRR) and immunoglobulin (Ig)-like domains in its extracellular region, as well as a transmembrane domain and a short cytoplasmic tail. LINGO-1 can form a ternary complex with Nogo-66 receptor (NgR1) and p75. Binding of LINGO-1 with NgR1 can activate the NgR1 signaling pathway, leading to inhibition of oligodendrocyte differentiation and myelination in the central nervous system. LINGO-1 has also been found to bind with epidermal growth factor receptor (EGFR) and induce downregulation of the activity of EGFR–PI3K–Akt signaling, which might decrease Purkinje cell survival. Therefore, it is possible that genetic variants of LINGO-1, either alone or in combination with other genetic or environmental factors, act to increase LINGO-1 expression levels in Purkinje cells and confer a risk to Purkinje cell survival in the cerebellum. Here, we provide a concise summary of the link between LINGO-1 and neurodegeneration and discuss various hypotheses as to how this could be potentially relevant to ET pathogenesis.